Policies And Legal Challenges In Small-Scale Gold Mining In Ghana That Hinders Its Formalisation; Stakeholders’ Perspective. - Kokofu, H.K. (University Of Ghana, 2021)
The mining industry in Ghana is divided into two primary forms: large-scale and small-scale mining. About 20 per cent of the country's mining industry is formalised, while over 80 per cent remain informal and unregulated. The rampant illegal activities associated with the small-scale mining industry has resulted in the degradation of the biophysical environment, posing severe developmental challenges. The country, through successive governments, has initiated moves to stop illegal mining activities all to no avail. This thesis sought to examine policies and legal challenges that hinder the formalisation of the small-scale gold mining sub-sector. The study employed a cross-sectional mixed approach and a systematic documentary review to attain its aims. Data gathering and analysis included both quantitative and qualitative methodologies, with 485 respondents. Focus Group Discussions were conducted at the District/Community levels and Key Informant Interviews with mining-related Institutions. The study collected quantitative data from the seven mining study districts. The study brought out many policies and laws that purport to govern small-scale mining in Ghana. It is important to note that the 1992 Constitution of Ghana is the primary source of law. However, several Acts of Parliaments and Policy statements are meant to regulate the mining sector. The results demonstrated a lack of institutional cooperation and collaboration, for instance, the mode of operation within the Minerals Commission (MC) and that of the Environmental Protection Agency (EPA). The results also suggested that budget allocations and staff strength are insufficient to enable effective monitoring. Moreover, some officers tasked with regulating small-scale miners' operations are found to be corrupt or compromised. A significant level of favouritism and nepotism were also detected. The lack of employment opportunities in mining communities influenced many people, mostly the youth, to engage in illegal activities. Furthermore, education and knowledge gaps contribute immensely to the indiscipline in the sub-sector. It was detected that the licensing regime is cumbersome and tedious; hence prospective miners are demotivated from acquiring permits before mining. The appreciation of illegal mining activities is also an issue. Whiles regulators (officialdom) are concerned with environmental degradation and its effects, the operator perceives the activities as a source of income and livelihood. Thus, socioeconomic considerations are powerful among the operators and members of the host communities. That leads to the question of ‘political will’ to genuinely fight the menace. The study recommends that regulatory agencies are resourced with adequate finances and logistics. Their human resource capacities must also be beefed up in numbers and efficiency. Critical regulators like the EPA should implement the provision in Section 23 of L.I. 1652 (1999) (Environmental Assessment Regulations), which requires the posting of reclamation bonds before the commencement of any mining activities. Furthermore, the coordination mechanisms among state and parastatals agencies such as the Minerals Commission, Land Commission, Forestry Commission, EPA, and the Water Resource Commission should be strengthened with enhanced transparency and efficiency. Policy and legislative formations and implementations are recommended to involve all industry stakeholders. Of particular interest are the traditional local authorities and community members. It is also necessary to upgrade the knowledge base of the direct operators through skills training and awareness creation.
PhD. Environmental Science
Keywords: Gold Mining; Ghana; Small-Scale